Eight Weeks of Aerobic Exercises Improves the Quality of Life in Healthy Aged Sedentary Men - Amini, Mojtaba; Mirmoezzi, Masoud; Salmanpour, Maryam; Khorshidi, Davood (International Journal of Sport Studies for Health, 2018)
Objectives: Advancements in health care systems and technologies have lowered the rate of mortality leading to an accelerated increase of aged population in Iran and worldwide. Therefore, the aim of the study was to investigate the effect of aerobic exercises on quality of life in healthy aged sedentary men. Methods: In this randomized controlled trial, 26 healthy aged men living in Qazvin nursing home participated voluntarily and were randomly assigned in two experimental (n = 13) and control (n = 13) groups. The experimental group performed aerobic exercise protocol three sessions a week for two months. The quality of life was assessed Using SF-36 health survey before and after exercise intervention. The data were analyzed by paired and independent t-tests. Results: The results suggested that quality of life was improved significantly after exercise program (P = 0.001), while no significant change was found in the quality of life in the control group (P = 0.34). Conclusions: Taken together, 8 Week of aerobic exercise program significantly improves the quality of life among the aged persons Additional research with a greater number of subjects and different exercise protocols are required to make crucial decisions regarding the effectiveness of similar exercise programs on aged persons.